Modulation of dopaminergic transmission and brain activity by frontotemporal tDCS: A multimodal PET-MR imaging study - Clara Fonteneau; Inés Merida; Jérome Redoute; Frédéric Haesebaert; Sophie Lancelot; Nicolas Costes; Marine Mondino; Jerome Brunelin (Brain Stimulation)
Background: Transcranial Direct Current Stimulation (tDCS) is a promising noninvasive intervention for schizophrenia, particularly when applied using a frontotemporal montage. Although significant clinical benefits have been reported, the variability in individual responses underscores the need for a more comprehensive understanding of its underlying neurophysiological mechanisms. Here, we used a simultaneous positron emission tomography (PET) and magnetic resonance imaging (MRI) approach (PET-MR) to investigate the effects of frontotemporal tDCS on dopamine transmission, cerebral perfusion, and white matter microstructural integrity in healthy individuals. Methods: In a double-blind, two-arm, parallel group study, 30 healthy volunteers were randomly allocated to receive a single session of either active (n = 15) or sham (n = 15) frontotemporal tDCS. The stimulation session was delivered during simultaneous multimodal PET-MR imaging, which combined PET with the [11C]raclopride radiotracer, Arterial Spin Labeling (ASL), and Diffusion Weighted Imaging. Results: PET [11C]raclopride analysis revealed a significant reduction in Non-Displaceable Binding Potential in the left executive striatal subregion 15 min after tDCS in the active group, compared to both baseline and the sham group. This finding suggests that frontotemporal tDCS may induce an increase in dopamine release. ASL analysis showed that active tDCS may reduce cerebral blood flow in the precuneus compared to sham stimulation. No significant effects of tDCS were observed on white matter microstructural integrity. Conclusion: This study provides new insights into the neurophysiological mechanisms of frontotemporal tDCS, paving the way for the optimization of therapeutic strategies for patients with dysregulated cortico-subcortical dopamine systems.